Auswertung von Blockchain-Inhalten zu Strafverfolgungszwecken - Koenen, Dr. Michael (Studien zum Strafrecht, 2023)
To help with the prosecution of criminal offenses related to the use of Bitcoin and other cryptocurrencies, it is possible to draw on publicly available data and analyze such data systematically. This is feasible because Bitcoin transaction data are essentially publicly available because of the way blockchain technology works. This dissertation seeks to answer the question whether such analyses of Bitcoin transaction data are permissible for the prosecution of criminal offenses under the law in two steps. First, it is discussed whether and at which point such analyses potentially infringe on fundamental rights in a way that requires justification. Second, it is examined whether the German Code of Criminal Procedure contains sufficient constitutional justification for an infringement of such rights. The decisive factor here is whether such an infringement is still minor in sense of sections 161, 163.